Metabolomic adaptations and genetic polymorphism in ecopopulations of Rhodiola linearifolia Boriss - Yerbay, Malika; Khapilina, Oxana N.; Turzhanova, Ainur S.; Otradnykh, Irina G.; Sedina, Irina A.; Mamirova, Aigerim; Korbozova, Nazym K.; Magzumova, Saule; Ashimuly, Kazhybek; Kudrina, Nataliya O.; Salnikov, Vitaly G.; Terletskaya, Nina V. (Frontiers in Plant Science, 2025)
Rhodiola linearifolia Boriss. (R. linearifolia) has long been used in folk medicine; however, research on its resources is limited due to the species inaccessibility for collection, and its potential for cultivation has not been previously explored. Understanding the synthesis of its valuable metabolites, as well as the factors influencing their accumulation under natural conditions, remains a relevant research objective. In this study, the metabolome of various ecopopulations of R. linearifolia was analyzed, and the relationship between metabolomic variations and genetic polymorphism was investigated using inter-simple sequence repeat (ISSR) and inter-primer binding site (iPBS) markers. Several significant positive correlations (r = 0.50–0.89) were observed. Significant genetic and metabolomic differences were identified among ecopopulations. Notably, experimental confirmation was obtained showing that ecopopulations with higher genetic polymorphism exhibited a more diverse metabolomic profile. These findings contribute to a deeper understanding of the species’ adaptation mechanisms and provide a foundation both for developing approaches to in situ conservation for R. linearifolia in situ in natural habitats, and optimizing introduction strategies for cultivation outside its natural range.